Three new constituents from the Tujia ethnomedicine Swertia punicea Hemsl. Issue 9 (3rd May 2023) - Yi, Pan; Li, Bin; Zafar, Salman; Ali, Sajjad; Sheng, Wen-Bing; Mao, Yu; Zhou, Fang; Chen, Wen-Ming; Tang, Yan-Ran; Peng, Cai-Yun; Choudhary, M. Iqbal; Rahman, Atta-ur-; et al.
Abstract: Three new constituents: 1, 5 R -dihydroxy-3, 8 S -dimethoxy-5, 6, 7, 8-tetrahydroxanthone (1), (3 S, 4 R, 16 S, 17 R )-3, 16, 23-trihydroxyoleana-11, 13(18)-dien-28-aldehyde-3- O - β -D-glucopyranoside (2), and new natural product ( S )-gentiandiol (3), along with 41 known compounds were isolated from Tujia ethnomedicine Shuihuanglian, namely, the whole plant of Swertia punicea . Structures of all these compounds were established through extensive spectroscopic techniques, namely 1D, 2D-NMR spectroscopy, HRESIMS analysis, and the absolute configuration of the new compounds was discerned by circular dichroism (CD) spectroscopy. Antioxidative effects of these compounds were evaluated by using the DPPH radical scavenging method, compounds 7, 9 and 14 showed antioxidant activities with IC50 values of 68.9, 50.8 and 48.2 μM, respectively. Graphical Abstract: UF0001